Pengaruh Sistem Pengukuran Kinerja, Motivasi dan Komitmen Organisasi terhadap Kinerja Manajerial Disnakertrans Provinsi Banten - Euis Mufahamah; Lestari Wuryanti; Muhammad Muhammad (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2022)
To find out how much influence the performance measurement system, work motivation and organizational commitment can improve managerial performance at Disnakertrans of Banten Province.This type of research is classified as qualitative research. The population in this study were employees at Disnakertrans of Banten Province. The sample was determined based on the non-probability sampling technique, with a total sample of 80 samples with online distribution. The analysis technique is Partial Least Square (PLS) using SmartPLS 3.0 software. The results of the study found the effect of performance measurement systems, work motivation and organizational commitment that can improve managerial performance at the Disnakertrans of Banten Province so as to improve excellent public services for the people of Banten.